Population Dynamics and Exploitation Rate of Coral Grouper Plectropomus leopardus in the Sarappo Islands, Pangkep Regency, South Sulawesi. (April 2019) - Ernaningsih,; Asbar,; Danial,; Hasrun, A; Jamal, M
Abstract: The coral grouper Plectropomus leopardus is a fish which plays important ecological roles in coral reef ecosystems. It is also a well-known and sought-after commodity in both local and export markets, leading to pressure on wild P . leopardus populations. The aim of this study was to describe the population dynamics and determine the exploitation rate of coral grouper ( P . leopardus ) populations in the Sarappo Islands, Pangkep Regency South Sulawesi, Indonesia. Coral grouper samples from Sarappo Island were caught using hand-line gear. Class length and weight data were analysed using the Bhattacharya method, von Bertalanffy model and Pauly empirical equation incorporated in the FiSAT II program to determine growth rate, mortality, and exploitation rate. The length frequency distribution of coral groupers sampled had length class means ranging from 20.0 cm to 57.1 cm. The 30.1 cm midpoint class had the highest catch frequency (162 fish) while the 57.1 cm class had the lowest frequency (3 fish). The length-weight relationship indicated an allometric growth pattern (b<3), with a growth coefficient (K) of 0.7. The total mortality (Z), natural mortality (M) and fishing mortality (F) were 3.03, 1.28, and 1.75, respectively, giving an exploitation rate E = 0.58 which exceeded the MSY limit (0.5). Coral grouper ( P . leopardus ) size structure was dominated by fish with immature gonad indices, increase in body length was faster than weight gain, fishing mortality was high, and the rate of exploitation exceeded the sustainable limit.